1998
DOI: 10.1001/archneur.55.4.517
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Autoimmune Features and Multiple Sclerosis

Abstract: Patients with MS with autoimmune features, including those with titers of antinuclear antibodies of 1:100 or less and/or antiphospholipid antibodies, are not different than others with MS, and therefore should not be excluded from clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
79
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 38 publications
(19 reference statements)
10
79
0
3
Order By: Relevance
“…The results of our study are in accordance with the investigations of Tournah et al [18] and Liedorp et al [25] who found low prevalence of ACL and B2GPI in MS patients, mainly IgM class. Many authors have suggested that the clinical features of MS could mimic APS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of our study are in accordance with the investigations of Tournah et al [18] and Liedorp et al [25] who found low prevalence of ACL and B2GPI in MS patients, mainly IgM class. Many authors have suggested that the clinical features of MS could mimic APS.…”
Section: Discussionsupporting
confidence: 93%
“…Some authors suggest that the detection of APL could have diagnostic and prognostic significance; however the data from the literature is very heterogenic. Some authors found positive anticardiolipin antibodies (ACL) in 5.3% [17] and 6.2% [18] of the studied MS patients. Sugyama and Yamamoto [19] detected IgM ACL in 44% and IgG ACL in 9% of MS patients.…”
Section: Introductionmentioning
confidence: 98%
“…The frequency of antinuclear antibodies ANA in patients with clinically definite MS varies from 2.5% to 81% of sera according to the study [5][6][7][8][9][10][11]. Most of these studies found no correlation between the presence of ANA and symptoms of SLE, although a correlation between ANA and MS disease activity was observed by Collard et al [10].…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies showed a prevalence of aCl in MS patients of 4.8-44% of cases [11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies examined comorbidity and MS. [3][4][5][6] Studies of autoimmune disease and MS did not identify any effect of autoimmune disease on clinical features or outcomes of MS. [3][4][5] Reports conflict regarding the association between smoking and disability progression. 6,7 Potential benefits of studying comorbidity in MS include improved prognostication; insights into the etiology and pathogenesis of MS; and the treatment of comorbidities as an avenue for improving outcomes.…”
Section: 2mentioning
confidence: 99%